Astrocyte elevated gene-1 is overexpressed in non-small-cell lung cancer and associated with increased tumour angiogenesis. (13th October 2017) - Ding, Qiuping; Chen, Yingrong; Dong, Shunli; Xu, Xuting; Liu, Jin; Song, Pengtao; Yu, Caihua; Ma, Zhihong
Abstract: OBJECTIVES: Astrocyte elevated gene-1 (AEG-1) functions to mediate angiogenesis, and its upregulation is responsible for tumour angiogenesis during cancer development. This study analysed AEG-1 expression in non-small-cell lung cancer (NSCLC) for association with NSCLC clinicopathological features and tumour angiogenesis. METHODS: The expression of AEG-1, vascular endothelial growth factor and intratumoural microvessel density (assessed using the expression of CD105) was detected by immunohistochemistry in 88 paired tumour tissue and adjacent normal tissue specimens obtained from NSCLC patients. The Kaplan–Meier curves were used for survival analysis through an online tool (http://kmplot.com/analysis/ ). RESULTS: AEG-1 was overexpressed in 61.3% of NSCLC tissues vs 6.8% (6/88) of normal tissues ( P  <   0.001). AEG-1 expression in NSCLC was significantly associated with advanced pTNM stage ( P  =   0.021), tumour dedifferentiation ( P  =   0.034), vascular invasion ( P  =   0.035), lymph node metastasis ( P  <   0.001) and poor overall survival ( P  =   0.024). Moreover, the expression of AEG-1 in NSCLC was associated with tumour angiogenesis; that is, vascular endothelial growth factor overexpression ( P  <   0.001) and intratumoural microvessel density ( P  <   0.001). CONCLUSIONS: This study demonstrates that AEG-1 expression is associated with NSCLC development, angiogenesis, progression and poor prognosis, indicating that the adjuvant therapy with antiangiogenic agent be adopted for the early postoperative period before the start of conventional chemotherapy in patients with AEG-1 overexpressed NSCLC.